Advances in the Iron-Catalyzed Direct Functionalizations of Heterocycles - Pradhan, Chandini; Punji, Benudhar (Synlett, 2022)
Direct functionalization of heterocycles is an advanced strategy for diversifying privileged and biorelevant heterocycle-containing molecules. Particularly, use of the most abundant transition metal, iron, as a catalyst makes this process highly cost-effective and sustainable. Recently, some progress has been realized towards the direct functionalization of heterocycles under iron catalysis. Herein, we present the developments in the C–H bond functionalizations and related reactions of various heterocycles by abundant iron salts. This Synpacts is categorized into different sections based on heterocycles being functionalized, and each section is discussed based on the type of reaction catalyzed by iron.1 Introduction2 Functionalization of Indoles2.1 Alkylation2.2 Alkenylation2.3 Other Reactions3 Oxindoles and Isatins3.1 C–C Bond Formation3.2 C–Heteroatom Bond Formation4 Pyridines and Furans5 Functionalization of Azoles6 Summary and Outlook
Keywords: alkylation; azoles; C–H functionalization; heterocycles; indoles; iron; mechanism